2005
DOI: 10.1186/1744-9081-1-21
|View full text |Cite
|
Sign up to set email alerts
|

Auditory processing in individuals with auditory neuropathy

Abstract: Background: Auditory neuropathy is a disorder characterized by no or severely impaired auditory brainstem responses in presence of normal otoacoustic emissions and/or cochlear microphonics. Speech perception abilities in these individuals are disproportionate to their hearing sensitivity and reported to be dependent on cortical evoked potentials and temporal processing abilities. The disproportionate loss of auditory percept in presence of normal cochlear function is suggestive of impairment of auditory neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…Results of the present study showed that the detection thresholds improved with decrease in modulation frequency (better thresholds for 8 Hz modulations than for 20 and 60 Hz). Similar results have been reported earlier [7] and the findings have been well explained [17]. …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Results of the present study showed that the detection thresholds improved with decrease in modulation frequency (better thresholds for 8 Hz modulations than for 20 and 60 Hz). Similar results have been reported earlier [7] and the findings have been well explained [17]. …”
Section: Discussionsupporting
confidence: 93%
“…Kumar and Jayaram [17], in a register-based retrospective study, reported a prevalence of 0.28% of ANSD in all the hearing impaired and 0.54% in individuals with permanent hearing loss. ANSD was diagnosed on the basis of criteria of Starr, et al [18] in this study.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Group I (normal control group) received glucose solution equivalent to the calorific value of ethanol (15 g of glucose/kg, ie, 5 mL of 30% glucose solution/100 g). Group II (hesperidin‐treated control group) received glucose solution equivalent to the calorific value of ethanol (15 g of glucose/kg, ie, 5 mL of 30% glucose solution/100 g) alone for the initial 30 days, then combined with hesperidin treatment at a dose of (50 mg/kg) dissolved in 1% dimethyl sulfoxide (DMSO) orally for another 30 days . Group III (ethanol‐fed group) received ethanol at a dose of (7.9 g/kg, ie, 5 mL of 20% ethanol/100 g) as an aqueous solution for 60 days by intragastric intubation (per os [po]) .…”
Section: Methodsmentioning
confidence: 99%